Dental intervention prior to and subsequent to the diagnosis of acute myeloid leukemia: case report - Iasminy Soares de OLIVEIRA; Naiane Maria do NASCIMENTO; Maria das Graças Afonso Miranda CHAVES; Tereza Cristina ESTEVES; Lídice Carolina LENZ E SILVA; Gisele Maria Campos FABRI (Faculdade São Leopoldo Mandic, 2022)
ABSTRACT Leukemia's are characterized by the proliferation of immature white blood cells, called blasts, in the bone marrow and / or blood. Among them, we highlight the Monocytic Acute Myeloid Leukemia, which represents a malignant neoplasm whose unnatural monoblast proliferation results in suppression of myeloid series cells. Oral manifestations are common, arising at the onset of the disease and are also associated with chemotherapy during treatment leading to complications that compromise oncotherapy. The present study deals with a patient with this type of aggressive leukemia, with oral complications of the disease and later, oncological treatment. It also give prominence the performance of the dental surgeon in distinct phases of the treatment emphasizing the importance of maintaining oral health in cancer patients. The presence of the Dentist in the multi-professional team contributes to the reduction of manifestations that occur both due to the disease and the treatment, ensuring a better quality of life for cancer patients and avoiding higher expenses to the health system.